Culture, Health & Sexuality : an international journal for research, intervention and care. (London : Taylor & Francis, 1999)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Institute of Education, University of London, 27-28 Woburn Square, London WC1M 0AA
Engels
Periodiek